Meta-analysis of Individual Patient Data After Kissing Stent Treatment for Aortoiliac Occlusive Disease. (February 2019) - Groot Jebbink, Erik; Holewijn, Suzanne; Versluis, Michel; Grimme, Frederike; Hinnen, Jan Willem; Sixt, Sebastian; Angle, John F.; Dorigo, Walter; Reijnen, Michel M. P. J.
Purpose: To evaluate short- and long-term technical and clinical outcomes after kissing stent treatment of aortoiliac occlusive disease (AIOD) based on an individual participant data (IPD) meta-analysis.Materials and Methods: A search of the Scopus database identified 156 articles on KS treatment of AIOD; of these 22 met the inclusion criteria. Authors of 19 articles with contact information were approached to join an IPD consortium. Eight author groups responded and 5 provided anonymized data for merging into an IPD database. The number of included procedures was equal before and after 2005. The primary study outcome was the cumulative patency at 24 months. Secondary outcomes were patency at up to 60 months, complications, and changes in Rutherford category and ankle-brachial index. The predictive value of stent protrusion length, pre-/postdilation, stent type, and patient demographics on primary patency were examined with Cox proportional hazard modeling; outcomes are reported as the hazard ratio (HR). The Kaplan-Meier method was employed to estimate patency rates.Results: In total, 605 (40.9%) of 1480 patients presented in the literature were included in the IPD analysis. The indication for intervention was intermittent claudication in 84.2% and critical limb ischemia in 15.8%. Lesions were classified as TransAtlantic Inter-Society Consensus (TASC) A or B in 52.8% and TASC C and D in 47.2%. The overall primary patency estimate was 81% at 24 months. Primary patency significantly increased after 2005 (p=0.005). Cox regression analysis revealed only age as a significant predictor of sustained primary patency (HR 0.60, p<0.005). Any previous endovascular intervention (HR 2.52, p=0.02) was the main predictor for loss of secondary patency; history of cardiovascular disease (HR 0.27, p=0.04) was the main predictor of sustained secondary patency.Conclusion: The kissing stent technique has a good safety profile and acceptable patency rates up to 2 years, even in TASC C and D lesions, supporting an endovascular-first approach for AIOD.